Solve the system of equation In three variables
2x+y-2z=-1 (1)
3x-3y-z=5 (2)
x-2y+3z=6 (3)
Answers
Answer:
Solve equation [3] for the variable x
[3] x = 2y - 3z + 6
// Plug this in for variable x in equation [1]
[1] 2•(2y-3z+6) + y - 2z = -1
[1] 5y - 8z = -13
// Plug this in for variable x in equation [2]
[2] 3•(2y-3z+6) - 3y - z = 5
[2] 3y - 10z = -13
// Solve equation [2] for the variable y
[2] 3y = 10z - 13
[2] y = 10z/3 - 13/3
// Plug this in for variable y in equation [1]
[1] 5•(10z/3-13/3) - 8z = -13
[1] 26z/3 = 26/3
[1] 26z = 26
// Solve equation [1] for the variable z
[1] 26z = 26
[1] z = 1
// By now we know this much :
x = 2y-3z+6
y = 10z/3-13/3
z = 1
// Use the z value to solve for y
y = (10/3)(1)-13/3 = -1
// Use the y and z values to solve for x
x = 2(-1)-3(1)+6 = 1
Solve the system of equation In three variables
2x+y-2z=-1 (1)
3x-3y-z=5 (2)
x-2y+3z=6 (3)
X=1. Y=-1 Z=1